Hepatitis C virus (HCV) infection in hemodialysis patients in the south of Jordan - Al-Jamal Mohammed; Al-Qudah Ameen; Al-Shishi Khaldoon; Al-Sarayreh Ameera; Al-Quraan Linda (Saudi Journal of Kidney Diseases and Transplantation, 2009)
Hepatitis C Virus (HCV) infection is a serious public health problem throughout the world. Patients with chronic renal failure are exposed to this infection. This could be due to a failure to identify carriers of this disease or because of lack of implementing truly effective safety measures in the dialysis units. This study was carried out in order to determine the prevalence of HCV infec-tion and possible risk factors for acquiring it in patients on maintenance hemodialysis (HD). A total of 120 patients, 63 males (52%) and 57 females (42%), who were on regular HD in three military hospitals in the south of Jordan were studied during the period between January 2007 and April 2008. A total of 34 patients (28%) were HCV positive of whom, 20 were males (58%). The mean age of the study participants was 52.9 years. The means of age of HCV positive and negative patients were 51.5 and 54.4 years, respectively. Statistical analysis showed that four risk factors including history of blood transfusion, history of kidney transplantation, history of other surgeries and duration on HD, had an important role in acquiring HCV infection. Although the prevalence of HCV infection in our study patients is lower than in many other countries in the region, we believe that the prevalence is still high and reflects a serious challenge, which needs further research to identify the causes and to establish a well organized prophylactic program.